The implementation of ipV6 human capacity development program for public sectors in Malaysia: a community ktp project - Hassan, Suhaidi; Budiarto, Rahmat; Che Mohamed Arif, Ahmad Suki; Sajat, Mohd Samsu (2015)
In order to remain an important part of the global Internet and to benefit from its growth, Malaysian organizations such as Government agencies, Internet and content service providers, and enterprises must embrace the transition to the new Internet Protocol version 6 or IPv6. The key to a successful transition is the readiness of human resource in adopting and adapting the new Internet technology. The KTP IPv6 Project attempts to assist Malaysian public sectors in building their human capacity in IPv6 technology. The initial aim of the project is to train some 500 public sector ICT personnel to familiarize and possible to certify them on the IPv6 technology. The internal training for trainer program started in April 2012 until end of August 2012. Besides that, this training was extended to train a group of external trainers from Politeknik Sultan Azlan Shah (PSAS) in Behrang, Perak. The PSAS trainers successfully completed their training and passed the locally-developed certification program called the Certified InterNetWorks Professional in IPv6 (CIPv6). Collaborations with government ministries, various state governments, local agencies and statutory bodies such as MARA and LHDN, as well as educational institutions such as universities, polytechnics and matriculation colleges have resulted in a series of training sessions which spanned until end of June 2014, with a total participation of 803 personnel, making an average of 80 personnel trained per month. With the progress, the project has successfully overachieved the Knowledge Transfer Program (KTP) project target to transfer IPv6 knowledge to more than 800 ICT personnel in the public sector.